2008
DOI: 10.1042/bst0360360
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the GPR40 locus: towards a molecular understanding

Abstract: GPR40 {FFAR1 [non-esterified ('free') fatty acid receptor 1]} is a G-protein-coupled receptor expressed preferentially in pancreatic beta-cells. GPR40 functions as a receptor for medium and long-chain fatty acids, and has been implicated in mediating both physiological and pathological effects of fatty acids on beta-cells. The GPR40 gene is encoded at an interesting chromosomal locus that contains several genes: at the 5'-end of the locus, located approximately 4 kb upstream of GPR40, is CD22, a gene encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Expression has also been detected in rat islets (Salehi et al, 2005;Feng et al, 2006). Such prominent ␤-cell expression was explained by a recent study on the promoter region of FFA1 that showed several highly conserved regions, one of which, HR2, is known to be a potent ␤-cell-specific enhancer of transcription (BartoovShifman et al, 2007;Ridner et al, 2008). Although none of the initial articles on the expression pattern of FFA1 were able to detect expression of the receptor within the glucagon-producing ␣-cells of islets, a more recent report using a prospective FFA1 antibody showed the receptor to colocalize with glucagon, suggesting that the receptor can be found within ␣-cells (Flodgren et al, 2007).…”
mentioning
confidence: 91%
“…Expression has also been detected in rat islets (Salehi et al, 2005;Feng et al, 2006). Such prominent ␤-cell expression was explained by a recent study on the promoter region of FFA1 that showed several highly conserved regions, one of which, HR2, is known to be a potent ␤-cell-specific enhancer of transcription (BartoovShifman et al, 2007;Ridner et al, 2008). Although none of the initial articles on the expression pattern of FFA1 were able to detect expression of the receptor within the glucagon-producing ␣-cells of islets, a more recent report using a prospective FFA1 antibody showed the receptor to colocalize with glucagon, suggesting that the receptor can be found within ␣-cells (Flodgren et al, 2007).…”
mentioning
confidence: 91%
“…The distribution of GPR40 suggests it may act to regulate pancreatic islet and neurological cell function [ 62 ]. Close to the GPR40 locus are the GPR41 and GPR43 genes encoding receptors activated by short-chain fatty acids [ 63 ]. GPCR receptors linked to GIP secretion are GPR120 and GPR40, expressed in K cells in the upper small intestine [ 64 , 65 ].…”
Section: The Endocrine System Of the Gut And The Control Of Appetitementioning
confidence: 99%
“…Three evolutionarily conserved sequences (HR1-HR3) are located upstream of the first exon. Among these, HR2 is a potent β-cell-specific enhancer and binds transcription factors, PDX1 and BETA2, and is thus responsible for regulating the transcriptional levels of the gene in β-cells (34,35). GPR40 belongs to class A GPRs, showing a typical 7-transmembrane (TM) domain structure spanning α-helices with 3 hydrophilic intracellular and 3 hydrophilic extracellular loops.…”
Section: Gene and Protein Information For Gpr40mentioning
confidence: 99%